European union internal market and labour law: friends or foes? (Antwerpen, 2009)
"The interaction between labour market regulation and the European Union’s internal market poses increasing challenges for both lawyers and policy makers throughout the European Union. From a policy point of view, the Lisbon Agenda and the reality of globalisation have driven the EU towards a reformative approach of labour law in the context of its employment strategy. In the legal arena, the mixture of different national labour standards and free economic exchange has turned explosive in the wake of EU enlargement. This book explores the intricate, complex, and sometimes contentious relationship between the European Union’s agenda for a free internal market and the protection of labour standards within the European Union. Its immediate focus is on recent legal developments, both in case law and in legislation. But these developments are addressed in a more general approach that seeks to give an overall background and context. The result of a conference held in the aftermath of the instantly famous cases of Laval and Viking, the book also reports on a panel discussion between stakeholders. "